Solusi dan Langkah Kongkrit dalam Penyelesaian Sengketa Pertanahan di Indonesia - Hadijah Haerani (Dinasti Research, 2025)
The existence of a conflict of interest in land causes land disputes. In order to realize the welfare of the community in the use and control of land, it is hoped that there will be improvements, both in the field of land use and land arrangement, with the realization of these improvements it is hoped that legal certainty in land in Indonesia will be born. The purpose of this study is to find out and describe solutions and concrete steps in resolving land disputes in Indonesia and dispute resolution mechanisms that can be taken both by litigation and non-litigation. This research is processed with a normative juridical approach method, namely by looking at law as a set of regulations/rules or doctrines that have a normative nature (law in book). The results of land disputes have complex roots, both from a legal and institutional perspective, laws and regulations need to be clarified and strengthened so that there are no legal weaknesses and loopholes that cause disputes. Dispute resolution can be done both by litigation and non-litigation.